Buy ology : truth and lies about why we buy - Lindström, Martin, 1970- (New York : Doubleday, 2008)
How much do we know about why we buy? What truly influences our decisions in today's message-cluttered world? An eye-grabbing advertisement, a catchy slogan, an infectious jingle? Or do our buying decisions take place below the surface, so deep within our subconscious minds that we're barely aware of them? Marketing guru Lindstrom presents the startling findings from his three-year, seven-million-dollar neuromarketing study, a cutting-edge experiment that peered inside the brains of 2,000 volunteers from all around the world as they encountered various ads, logos, commercials, brands, and products. His startling results shatter much of what we have long believed about what seduces our interest and drives us to buy.--From publisher description.
A rush of blood to the head : the largest neuromarketing study ever conducted -- This must be the place : product placement, American Idol, and Ford's multimillion dollar mistake -- I'll have what she's having : mirror neurons at work -- I can't see clearly now : subliminal messaging, alive and well -- Do you believe in magic? : ritual, superstition, and why we buy -- I say a little prayer : faith, religion, and brands -- Why did I choose you? : the power of somatic markers -- A sense of wonder : selling to our senses -- And the answer is : neuromarketing and predicting the future -- Let's spend the night together : sex in advertising -- Conclusion : brand new day.
Includes bibliographical references (p. 217-229) and index.
Fourth year high school and above
Keywords: Neuromarketing; Consumer behavior -- Psychological aspects; Shopping -- Psychological aspects; Marketing -- Psychological aspects